Métodos combinados na conservação de manga ‘Ubá’ - Sousa, Jessica Caroline Correa de Oliveira (2019)
The demand for a more natural and healthier eating has motivated the investigation of ways to preserve fresh food as long as possible. The use of natural coatings has been used for postharvest conservation of different types of fruits and vegetables, integers or processed, in order to extend shelf life and maintain their physical, sensory and microbiological qualities throughout storage. Cold storage is also widely used in conjunction with this technique, particularly in climatic fruits and warmer climates. This paper aims to study postharvest conservation of mango 'Ubá' using natural coatings based on beeswax, carboxymethylcellulose, carnauba wax and cassava starch combined with refrigerated storage. The control (mango without coating) and coated mangoes were evaluated for physicochemical and rheological characteristics at fruit harvest (0 days) and during storage (7, 14, 21 and 28) days at 15 ° C, plus 3 days, at each interval, at 25 ° C, totaling the storage time at 3, 10, 17, 24, 28 and 31 days. The coatings used had positive effects on fruit preservation, compared to control fruits, delaying fruit ripening, like acidity reduction, pH and soluble solids increasing and pulp firmness loss. The best performing coatings were beeswax, carboxymethylcellulose and cassava starch solutions. However, beeswax coated fruits did not mature satisfactorily. The carboxymethylcellulose and cassava starch solutions were the most suitable for the proposed storage conditions.